Description of last instar larva and pupa of Chaeridiona picea Baly, 1869 and Oncocephala quadrilobata (Guerin, 1844) (Coleoptera: Chrysomelidae: Cassidinae: Oncocephalini) from India - Świętojańska, Jolanta; Chorzępa, Magdalena; Ghate, Hemant (Zootaxa, 2006)
The last instar larva and pupa of Chaeridiona picea Baly, 1869 and Oncocephala quadrilobata (Guérin, 1844) are described and figured in detail. Measurements of body and chaetotaxy of head, mouthparts, legs, dorsal and ventral side of the body are given for both the species. These descriptions of immature stages are the first for the tribe Oncocephalini. The larvae of both Chaeridiona and Oncocephala differ from other genera of leaf-mining hispinae in the absence of thoracic lateral scoli and in the structure of the last tergite which seems to be characteristic for each particular genus. The pupae of the described species are distinguished by presence of very long spiracles on the fifth abdominal segment which seems to be adaptation to the leaf-mining behaviour. The shape of apical tergite of the pupae is different for particular species and is probably also a character diagnostic for the genera.